Social adaptation and its relationship to motor learning in physical education and sports classes for secondary school students - FAID, abdrazek (sports creativity, 2025)
The social adaptation and its relationship with the physical learning for high school student in some secondary school in m'sila . This study is meant for knowing the relationship between the social adaptation and physical learning in the physical education sessions for high school students this research has been applied on the first year students knowing that the high school phase is a new phase in students lives it means the beginning of a new structural phase ,and this change in school in environment has an automatic and direct relationship with the adaptation factor ,and the person's ability to surrender to,new changes . This survey has been applied on 314 first year students ,and this sample has been selected randomly from total 10 secondary schools in m'sila ,taking into consideration the geographical division of the city . The researcher has used the descriptive method .after applying using the research tools (instruments) ,the criteria of social adaptation ,but concerning the physical learning they relied on the results of the research. Finally ,we conchide , that there is a mutual and positive relationship between the social adaptation and the physical learning in the physical education sessions for the high school students.